The Development of Problem-Based Mobile Augmented Reality Application to Enhance Creative Problem-Solving Skills for Undergraduate Students - Wongklang, Piyanoot; Wipatsopakron, Jirasak (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study aims to develop a problem-based mobile augmented reality (AR) application to enhance creative problem-solving skills among undergraduate students. The research involves an experiment conducted on a sample group of 30 undergraduate students enrolled in the maintenance of computers and audio-visual equipment course, selected through a simple random sampling method. The instruments used in the study included structured interview questions, needs assessment questionnaires, quality evaluation of mobile applications, evaluation of the learning plan, measurement of creative problem-solving ability, and satisfaction surveys. The data obtained were analyzed using mean, standard deviation, dependent t-test, and effect size statistics. The findings demonstrated that the developed mobile application achieved the highest quality level, with an average value of 4.62 (SD = 0.64). The mobile application efficiency reached 75.48 out of 75.16, meeting the established threshold of 75 out of 75. Using the mobile application led to statistically significant improvements in creative problem-solving skills after the learning process, with scores higher than those before learning at the 0.05 level. The effect size was 6.61, indicating a large impact. Additionally, student satisfaction with the mobile application was reported as the highest.